The modification and extension of the strong equivalence principle - Jian’an Wang (ScienceOpen Research)
In this paper, the strong equivalence principle is analyzed by the gravitational mechanism of etheric pressure, and the conclusion is drawn that an object at rest in a uniform gravitational field of a certain strength is equivalent to moving in a straight line in a uniform etheric space with a certain speed (not a certain acceleration). According to the etheric pressure gravitational mechanism, gravitational field is a scalar field (energy field or etheric field), and gravity is caused by the asymmetric density distribution of space energy (etheric), resulting in the asymmetric etheric pressure on the object at rest in space. According to this gravitational mechanism, if the gravitational field strength (energy density) of space is the same at every point, then objects in that space will not generate gravity. Therefore, a uniform gravitational field is not equivalent to a uniformly accelerated non-inertial system. The inequivalence between the uniform gravitational field and the uniformly accelerated non-inertial system is also reflected in: the object at rest in the gravitational field does not change in time, length, and mass, but the object at rest in the non-inertial system of accelerating motion (relative to the ether) has been slowing down in time, shortening in length, and increasing in mass; a charged particle at rest in a gravitational field does not radiate electromagnetic waves outward, but a charged particle at rest in a non-inertial system in accelerated motion (relative to the ether) will radiate electromagnetic waves outward continuously. The paper points out that the experimental fact of equivalence between gravity fields and velocity (rather than acceleration) in terms of time dilation has proven the equivalence between uniform gravity fields and inertial systems with uniform motion (rather than non-inertial systems with uniform acceleration). It further deduces that gravity fields are equivalent to velocity in terms of the increase in the inertial mass effect of objects, and gravity fields are equivalent to velocity in terms of the contraction effect of the electron orbit radius of atoms. The gravitational force experienced by a stationary object in a gravitational field with a gradient of field strength is equivalent to the inertial force experienced by the same object when it undergoes linear acceleration in the Ether space. The Ether (energy) field with a gradient of field strength generated by a fluid whose flow velocity decreases perpendicular to its motion is equivalent to the gravitational (energy) field with a gradient of field strength. Using these modified and extended equivalence principles, the author explains Newton’s bucket experiment, explains the physical mechanism of inertial force and inertial centrifugal force, explains the Casimir effect, and explains what reference system the flow rate of fluid in Bernoulli equation is relative to, and why the higher the flow rate is relative to the reference system, the lower the pressure.